Cambios en el Índice de Hígado Graso con una intervención con dieta mediterránea: seguimiento de 6 años del ensayo PREDIMED-Málaga. - Cueto-Galán, Raquel; Barón-López, Francisco Javier; Valdivielso-Felices, Pedro; Pinto, Xavier; Corbella, Emili; Gómez-Gracia, Enrique; Warnberg, Julia (Elsevier, 2017)
This study analyzed the effect of a Mediterranean diet (MedDiet) supplemented with extra virgin olive oil (EVOO) or nuts on the Fatty Liver Index (FLI) compared to a low-fat diet. Participants were high-risk individuals without cardiovascular disease, and data were collected over six years. Results showed that the MedDiet+EVOO and MedDiet+Nuts groups had slower FLI increases compared to the control, with improved BMI and waist circumference trends. The findings suggest the MedDiet could slow NAFL progression, although further research is needed.
Changes in fatty liver index after consuming a Mediterranean diet: 6-year follow-up of the PREDIMED-Malaga trial.
https://www.sciencedirect.com/journal/medicina-clinica/publish/open-access-options
Keywords: Dieta en enfermedades; Hígado - Enfermedades - Aspectos nutricionales; Fatty liver; Intervention studies; Mediterranean diet; Primary prevention